Neuronal expression of S100B triggered by oligomeric Aβ peptide contributes to protection against cytoskeletal damage and synaptic loss - Saavedra, Joana; Nascimento, Mariana; Figueira, António J.; Oliveira da Silva, Marina I.; Gião, Tiago; Oliveira, João; Liz, Márcia A.; Gomes, Cláudio M.; Cardoso, Isabel (Frontiers in Molecular Neuroscience, 2025)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder characterized by the intracellular deposition of Tau protein and extracellular deposition of amyloid-β peptide (Aβ). AD is also characterized by neuroinflammation and synapse loss, among others. The S100 family is a group of calcium-binding proteins with intra- and extracellular functions, that are important modulators of inflammatory responses. S100B, which is upregulated in AD patients and the most abundant member of this family, was shown to inhibit in vitro the aggregation and toxicity of Aβ42, acting as a neuroprotective holdase-type chaperone. Although S100B is primarily produced by astrocytes, it is also expressed by various cells, including neurons. In this work, we investigated if S100B neuronal expression is triggered as a response to Aβ toxic species, to provide protection during disease progression. We used the AD mouse model AβPPswe/PS1A246E to show that neuronal S100B levels are significantly higher in 10-month-old animals, and cellular assays to demonstrate that Aβ oligomers significantly increase S100B expression in SH-SY5Y cells, but not monomeric or fibrillar Aβ. Using primary cultures of rat hippocampal neurons, we showed that S100B partially reverts Aβ-induced cofilin-actin rods (synapse disruptors), and rescues the decrease in active synapses and post-synaptic marker (PSD-95), imposed by Aβ peptide. Altogether, these findings establish the neuroprotective activity of S100B in response to proteotoxic stress in cells, highlighting its chaperone function as a crucial factor in understanding proteostasis regulation in the diseased brain and identifying potential therapeutic targets.